Drinking water treatment through pre-ozonation and membrane filtration - Muhammad Hasif Jemain (Nanyang Technological University, 2022)
Ceramic membrane (CM) applications are gaining popularity in water treatment. It has a better material integrity which can withstand high pressured fluxes and is tolerant to a greater pH and temperature range than most polymeric membranes. CMs are also resistant harsh chemical conditions during cleaning. However, CMs are not exempted from membrane fouling. Most irreversible membrane foulants are non-removable through cleaning treatments such as backwash, or chemical treatment and even through ozonation. However, advanced oxidative process (AOP) used in tandem with ozone treatment has the potential to mitigate membrane fouling properties and prolong life cycle of the membranes. Catalytic ozonation membranes were fabricated such as the Fe3O4/PVDF and CeTi-CeCCM.This catalytic ozonation process is initiated by an hydroxide ion which then produces a series of chain reaction producing hydroxyl radicals and intermediate compound radicals. These create new possible pathways for the irreversible foulants to be broken down. This project is done in 3 stages. First was the recovery of ‘dirty’ CM newly opened from packaging using ozone treatment. Second, ozone pre-treatment optimization run of ferric chloride-coagulated settled water (SW) was conducted. Lastly, the effects of catalytic properties of ferric-doped membranes during ozone treatment were analysed. Results suggested that ozone as pre-treatment slows down the rate of membrane permeability and catalytic properties of a ferric-doped membrane showed greater production of hydroxyl radicals than non-doped aluminium oxide membrane. Results also suggested ferric-doped membranes increased physical rejection of the water. However the study was limited due to the reactivity of tert-butanol (TBA) and ozone. Varying pH conditions were also not tested to understand the optimal conditions for hydroxyl radicals production. A more comprehensive study of the membrane foulant matrix would also help provide a better understanding of the its reactivity with catalytic ozone treatments.